Time inconsistency and overdraft use: Evidence from transaction data and behavioral measurement experiments - Andrej Gill; Florian Hett; Johannes Tischer (Deutsche Bundesbank, 2022)
Households regularly fail to make optimal financial decisions. But what are the underlying reasons for this? Using two conceptually distinct measures of time inconsistency based on bank account transaction data and behavioral measurement experiments, we show that the excessive use of bank account overdrafts is linked to time inconsistency. By contrast, there is no correlation between a survey-based measure of financial literacy and overdraft usage. Our results indicate that consumer education and information may not suffice to overcome mistakes in households' financial decision-making. Rather, behaviorally motivated interventions targeting specific biases in decision-making should also be considered as effective policy tools.
Keywords: D14; D90; G51; G53; 330; Household Finance; Paycheck Sensitivity; Fintech; Time Inconsistency; Time Preferences; Experiment; Behavioral Measurement